ENHANCING THE STABILITY OF THE TIMBER HARVESTING MACHINE OF MANIPULATOR TYPE BY USING AN ACTIVE SUSPENSION SYSTEM - Bogdanov, Evgenii Nikolaevich; Bagautdinov, Ildar Nyrgaiazovich; Zhilin, Stepan Sergeevich (Journal of Applied Engineering Science, 2015)
The paper represents technique and calculation of the timber harvesting machine stability when using an active suspension system that leads to enhancement of stability and productivity increase at the expense of safe work.
Keywords: Stability; Undercarriage frame; Manipulator; Feller buncher; Mathematical modeling